Component Processes of Decision Making in a Community Sample of Precariously Housed Persons: Associations With Learning and Memory, and Health-Risk Behaviors - Baitz, Heather A.; Jones, Paul W.; Campbell, David A.; Jones, Andrea A.; Gicas, Kristina M.; Giesbrecht, Chantelle J.; Loken Thornton, Wendy; Barone, Carmelina C.; Wang, Nena Y.; Panenka, William J.; Lang, Donna J.; Vila-Rodriguez, Fidel; et al. (Frontiers in Psychology, 2021)
The Iowa Gambling Task (IGT) is a widely used measure of decision making, but its value in signifying behaviours associated with adverse, “real-world” consequences has not been consistently demonstrated in persons who are precariously housed or homeless. Studies evaluating the ecological validity of the IGT have primarily relied on traditional IGT scores. However, computational modelling derives underlying component processes of the IGT, which capture specific facets of decision making that may be more closely related to engagement in behaviours associated with negative consequences. This study employed the Prospect Valence Learning (PVL) model to decompose IGT performance into component processes in 294 precariously housed community residents with substance use disorders. Results revealed a predominant focus on gains and a lack of sensitivity to losses in these vulnerable community residents. Hypothesized associations were not detected between component processes and self-reported health-risk behaviours. These findings provide insight into the processes underlying decision making in a vulnerable substance-using population and highlight the challenge of linking specific decision making processes to “real-world” behaviours.